The Messel Pit: Window into a Greenhouse World - Krister Smith (Geoconservation Research)
Anthropogenic climate change may result, within 200 years, in warm and equable climatic conditions not experienced on Earth for tens of millions of years. Ancient ecosystems under such “greenhouse” conditions may be seen as natural experiments, and their study may help us anticipate the future, should mediation fail. The Messel Pit, a UNESCO World Heritage site in Germany, is a fossil-rich deposit laid down in the Eocene under such a greenhouse climate. Fossils of all major groups of terrestrial (including freshwater) organisms are preserved. These allow us to study their relationships, reconstruct species diversity, explore how modern groups of plants and animals evolved, and how they interacted with their environment. Examples are presented of trophic chains and reproductive behavior. Thanks to the exceptional quality and abundance of its fossils, Messel arguably offers the most detailed insight into the terrestrial ecosystem of the Eocene.